Etiopathogenetical approaches to the diagnosis and treatment of acute and chronic central serous chorioretinopathy. Review - A. G. Shchuko; A. N. Zlobina; T. N. Iureva (Oftalʹmologiâ)
Central serous chorioretinopathy is still considered a disease with uncomletely studied etiology and pathogenesis, so there is no single approach to the treatment of this condition. In review the known factors of central serous chorioretinopathy, as well as the basic theories of its formation are presented. In addition, the methods of diagnostics and used to date methods of treatment for both acute and chronic central serous chorioretinopathy are described.